সতী ও স্বতন্তরা : বাংলা সাহিত্যে নারী, দ্বিতীয় খণ্ড - আখতার, শাহীন. (ঢাকা : দিব্য প্রকাশ ; ওয়াটার লিলি, 2007)
Collection of poems, fiction, and articles on women as evident in Bengali literature since 19th century.
Includes bibliographical references and indexes.
বিদিত
In Bengali.
Keywords: Bengali literature -- History and criticism; Bengali literature -- 19th century; Bengali literature -- 20th century; Women in literature